STUDI KEBUTUHAN ANGKUTAN UMUM PENUMPANG PERKOTAAN DI KOTA PALU (Studi kasus: Trayek Mamboro - Manonda) - Febrianti AD, Ana; Mashuri, Mashuri (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
One of cause of public transport services is not optimal is the incompatibility between the number ofpublic transport with passenger numbers to be served. Incompatibility of the number of publictransport with the number of passengers served would also affect the income of public transportoperators. The purpose of this study is to estimate the needs of the urban public transport routesMamboro – Manonda, Palu City based on the number of passengers along the route. Primary datacollection survey was conducted in January of 2010 for 3 days at each peak morning, afternoon andevening. Survey of primary data through questionnaires and enumeration of the number ofpassengers. The primary data include the number of passengers up and down along the route, roundtrip time of the public transport, time headway of each the public transport. Secondary data includepath of Mamboro – Manonda route, the number of public transportation of Mamboro – Manondaroute. Methods and standards used in estimating the number of public transportation refer to theTechnical Guidelines for the delivery of the Urban Passenger Transport, 2002, the Ministry ofTransportation, Republic of Indonesia.The results have been found several conclusions as follows: there are differences in the needs ofpublic transport in every peak hour morning, afternoon and evening, number of public transport thatoperates not according to the number of passengers served, increasing the number of publictransport is not required for the next few years.